2020
DOI: 10.1080/08869634.2020.1786332
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of education, awareness, and knowledge of dentists and physical therapists in the treatment of temporomandibular disorders

Abstract: Objective: Multidisciplinary and interprofessional collaboration has been implicated in the effective treatment of temporomandibular disorders (TMD). The objectives of this study were to compare the education, awareness, and knowledge of Filipino dentists and physical therapists (PT) in terms of TMD. Methods: A 30-item structured online questionnaire was used on recruited PT and dentists from January 2019 to December 2019. Welch's t-test was used to compare the education, awareness, and knowledge of the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…Although various medications are used in the management of TMD, there has been, generally, a paucity of evidence to support a standardized regimen and the best class of medications to be used [ 40 , 52 ]. Therefore, the clinical decision still lies mainly with the clinicians’ experience and comfort [ 53 ], tailored to the patient’s best individual needs.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Although various medications are used in the management of TMD, there has been, generally, a paucity of evidence to support a standardized regimen and the best class of medications to be used [ 40 , 52 ]. Therefore, the clinical decision still lies mainly with the clinicians’ experience and comfort [ 53 ], tailored to the patient’s best individual needs.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…In the Philippine context, age and number of years in college might increase knowledge due to the structure of the educational system. In a Filipino family, females are also favored to go to universities as opposed to males who are expected to work [26]. Proximity to the university and being Filipino are also significant in terms in knowledge acquisition as teachers in healthcare professions can provide valuable information better [27].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in international standards for each profession can also be a barrier to effective collaboration. A recent study of Filipino dentists and physical therapists showed low education and knowledge among dentists and physical therapists (20). Looking to the future, more practical opportunities for interprofessional training and collaboration among physical therapists, dentists and physicians during both pre-doctoral education and post-doctoral practice is one way to address such discrepancies.…”
Section: Interprofessional Collaboration and Trainingmentioning
confidence: 98%
“…Another opportunity for refinement concerns the contribution of structures and systems outside of the masticatory system such as the cervical spine and central nervous system which can contribute to the persistence of pain in individuals with TMD. The connection between the cervical spine and TMD is well-documented in the literature (19)(20)(21)(22)(23)(24)(25) but is minimally addressed in the dentistry-focused DC/TMD. Similarly, the central nervous system provides an accessible link between DC/TMD Axis I and II symptoms without guidance for inclusion in rehabilitation.…”
Section: Introductionmentioning
confidence: 99%